Yield performance of bushing snap bean genotypes in two environments - Gomes, Guilherme (2016)
In Parana state are little information about the yield performance of bushing snap bean genotypes in different environments. The study aimed to evaluate the performance of bush snap beans genotypes in two environments. The experimental design was randomized blocks, in 3x2 factorial design, with three genotypes (UEL 1, UEL 2 and Feltrin Vicenza Amarelo Baixo®) and two environments (Tamarana and Londrina, both in Parana state), with four replications. The following parameters were evaluated: days to flowering, average number of pods per plant, average weight of pods per plant and yield of pods. Except for days to flowering, in which isolated effects of genotype and environment were checked, it was found a significant interaction between genotype x environment for the other parameters. To UEL 1, the average number of pods per plant was higher in Londrina, with direct influence on the pods yield. The component average weight of pods per plant was higher and determiner the pods yield in Tamarana for the UEL 2 and Feltrin genotypes. The genotype x environment interaction showed different responses of genotypes evaluated to the environment in relation to numbers of pods per plant, weight of pods per plant and pods yield.